Testing of Various Types of Plastic Materials in Plastic Waste Processing Device using Coconut Shell Fuel - Didy Hikmah Utama; Saipul Bahri Daulay; Ainun Rohanah (Universitas Sumatera Utara, 2016)
The decrease of fossil resources and increase population are very contradictive to energy consume for human life and social economy activity. So, alternative energy is needed which environment friendly by the use of plastic waste as fuel. This research as aimed to compare fuel from plastic (Polyethylene), cosmetic bottle (HDPE) and mineral water bottle (PET) with kerosene. This research was done in Agriculture Engineering Laboratory, and in Physical Chemistry Laboratory of MIPA and Heat Engine Laboratory Faculty of Engineering in August 2014 until finish using completely randomized non factorial design with plastic (Polyethylene), cosmetic bottle (HDPE) and mineral water bottle (PET). The parameters analysed were yield, value of heat and viscosity. The results, showed that fuel nearly the same with kerosene was P2 (cosmetic bottle) with heat of 10.578,6 kcal/Kg and viscosity of 0,940 cP. Keywords : Plastic waste, Polyethylene, HDPE, PET